Resistance of three Nigerian hardwoods to decay caused by brown-and white-rot basidiomycetes (2006)
Assessment of resistance of untreated and n - hexane extract wood blocks of Afzella africana, Nesogordonia papaverifera end Teclona grandis to decay caused by Fomes lognosus, Lentinus Lepideus and GloephyIlum trabeum using percent weight loss was carried out . The study revealed that the durability of these wood species related primarily to the presence of the extractives in the heartwood. Removal of the extractive from the heartwood increases the susceptibility of the wood species to decay. The weight losses for A. africana were 56.3%, 58.1% and 58.7% for F. lignosus, L. lepideus and G. trabeum respectively. N. papaverifera showed weight losses of 57.2%, 58.3% and 58.9% for F. Iignosus, L. lepideus and G. trabeum respectively while T. grandis decreased in weight by 64.2% 67.4% and 78.2% for L. lepideus, G. trabeum and F.lignosis, respectively.